2020
DOI: 10.35609/jfbr.2020.5.3(3)
|View full text |Cite
|
Sign up to set email alerts
|

Tax Policy and Foreign Direct Investment: A Regime Change Analysis.

Abstract: Objective – Tax policies play significant role in the direction of foreign direct investments. We investigate the proposition that tax policies enacted by military and democratic regimes differ on the influence the foreign direct investments. Methodology/Technique – Our hypotheses are tested using the error correction model as we compare the impact of tax policies on flow foreign direct investments in Nigeria between two dispensations: military rule from 1983 to 1999 and democratic rule from 1999 to 2017. Pane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…On a general note, the operational impact of the model outweighs the cost [31], [32] and has been categorized as effective over other security models in the business context, telecommunication organizations such as At&T have confirmed that its reduces organizational risk and closes lapses in cloud control mechanisms, more so, it reduces the risk of a data breach, thus saving organizations the cost of litigations and unauthorized use of customer data for espionage, and more importantly, it reduces the risk of security breach both on-premise and virtually. Definition of Zero trust Various definitions have been coined around the Zero Trust Model, a common phrase in the definition is trust and this extends to the users, devices, networks, and other variables that interface within and outside the perimeters of an organization"s network.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On a general note, the operational impact of the model outweighs the cost [31], [32] and has been categorized as effective over other security models in the business context, telecommunication organizations such as At&T have confirmed that its reduces organizational risk and closes lapses in cloud control mechanisms, more so, it reduces the risk of a data breach, thus saving organizations the cost of litigations and unauthorized use of customer data for espionage, and more importantly, it reduces the risk of security breach both on-premise and virtually. Definition of Zero trust Various definitions have been coined around the Zero Trust Model, a common phrase in the definition is trust and this extends to the users, devices, networks, and other variables that interface within and outside the perimeters of an organization"s network.…”
Section: Literature Reviewmentioning
confidence: 99%